TRANSCULTURAL ANALYSIS OF AAMER HUSSEIN’S NOVEL ANOTHER GULMOHAR TREE (Contemporary Journal of Social Science Review, 2024)
This research examines the transcultural elements in the novel Another Gulmohar Tree by Aamer Hussein. The novel's themes and characters are examined through the lens of transculturalism in this research. The aim of this research is to analyze the theme of identity, love and cultural exchange by applying the theory of transculturalism by Wolfgang Welsch. This process investigates that how in the context of unequal power dynamics; cultures interact and form a new, hybrid culture. It explores the idea of transculturation within the framework of postcolonial literature. This study explains how transculturalism, as a framework, highlights themes of cross-cultural migration and identity in the novel. Specifically, it focuses on the interaction between the characters Usman and Lydia, who are from different cultural backgrounds and who face the challenges and opportunities of transcultural interchange through their relationship and migration. The objectives of this research are about two things: first, to analyze how the interaction between Usman and Lydia highlights the challenges and opportunities of cultural integration and adaptation; and second, it will investigate how the novel approaches the issues of identity and love from a transcultural perspective. Methodologically, this study employs a qualitative approach based on Wolfgang Welsch's transcultural theory, which suggests that cultures are dynamic and continuously influenced by migration and globalization. This theoretical framework is applied to understand how Another Gulmohar Tree reflects the fluid nature of cultural identities and the enriching potential of transcultural interactions.